2015
DOI: 10.1007/s13181-015-0525-5
|View full text |Cite
|
Sign up to set email alerts
|

Naloxone Administration in US Emergency Departments, 2000–2011

Abstract: Rates of opioid overdose and opioid-related emergency department (ED) visits have increased dramatically. Naloxone is an effective antidote to potentially fatal opioid overdose, but little is known about naloxone administration in ED settings. We examined trends and correlates of naloxone administration in ED visits nationally from 2000 to 2011. Using data from the National Hospital Ambulatory Medical Care Survey, we examined ED visits involving (1) the administration of naloxone or (2) a diagnosis of opioid o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 36 publications
1
13
0
Order By: Relevance
“…These include deaths from multiple drugs and prescription drugs, injection of heroin or prescription opioids, and the use of opioids for pain or in combination with other pain medications (19)(20)(21)(22)(23)(24)(25)(26). Furthermore, the age-adjusted opioid-overdose death rates have steadily risen in rural areas for the past twenty years and data reveal that rural residents are less likely than urban residents to be administered naloxone during an opioid overdose in US emergency departments (27). Additionally, from 2007 to 2015, drug-overdose death rates were higher in rural than in urban counties, though this pattern recently reversed direction (28), with the steepest rise from 2016 to 2017 occurring among African Americans (29).…”
Section: Introductionmentioning
confidence: 99%
“…These include deaths from multiple drugs and prescription drugs, injection of heroin or prescription opioids, and the use of opioids for pain or in combination with other pain medications (19)(20)(21)(22)(23)(24)(25)(26). Furthermore, the age-adjusted opioid-overdose death rates have steadily risen in rural areas for the past twenty years and data reveal that rural residents are less likely than urban residents to be administered naloxone during an opioid overdose in US emergency departments (27). Additionally, from 2007 to 2015, drug-overdose death rates were higher in rural than in urban counties, though this pattern recently reversed direction (28), with the steepest rise from 2016 to 2017 occurring among African Americans (29).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have suggested that the combined application of naloxone and opioids may reduce opioid-related side effects. [13][14][15] A combination of low-dose epidural naloxone at 0.25 μg•kg −1 •h −1 with fentanyl is valid in attenuating undesired side effects, especially PONV, besides enhancing analgesia during the early postoperative period. [16] Intravenous infusion of naloxone at a low dose of 0.25 to 1.65 μg•kg −1 •h −1 reduces PONV in children, with greater evidence of its effectiveness as a preventative strategy than in the treatment of existing pruritus.…”
Section: Hy and Xg Contributed Equally To This Workmentioning
confidence: 99%
“…Naloxone, an opioid antagonist, has long been used to diagnose and manage respiratory depression related to opioid overdose. [ 10 ] Recently, some studies indicated that the combined application of naloxone and opioid may reduce opioid-related side effects. A study carried out by Xiao et al [ 11 ] proved that naloxone infusion could prevent the acute opioid tolerance, provide a quicker recovery of bowel function, and reduce the length of hospital stay after open colorectal surgery.…”
Section: Introductionmentioning
confidence: 99%